The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1177/0003489419898717
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Nasal Fluid Biomarkers and Symptoms in Patients with Persistent Allergic Rhinitis

Abstract: Objectives: This study investigated whether the biomarkers present in nasal fluid reflect the severity of symptoms in patients with persistent allergic rhinitis (PAR). Methods: We enrolled 29 PAR patients complaining of nasal symptoms and testing positive to skin prick test. Patients’ total nasal symptom score (TNSS) was measured and their nasal lavage fluid (NALF) was collected. The levels of biomarkers including Clara cell protein 16 (CC16), tryptase, and interleukin 5 (IL-5) in NALF were determined via enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Similar to viral infections, patients with allergic rhinitis have decreased levels of SCGB1A1 in the nasal fluid: children with birch pollen allergy show decreased levels of SCGB1A1 in the nasal fluid during and out of birch pollen season compared to healthy controls 48 . In addition, it has been shown in patients with intermittent 49 and persistent 38 allergic rhinitis that the SCGB1A1 levels in nasal fluid within one hour after allergen challenge correlate inversely with the symptoms of rhinitis. To the best of our knowledge, the role of other SCGBs in allergic rhinitis has not yet been described.…”
Section: Secretoglobins In Diseases Of the Upper And Lower Airwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to viral infections, patients with allergic rhinitis have decreased levels of SCGB1A1 in the nasal fluid: children with birch pollen allergy show decreased levels of SCGB1A1 in the nasal fluid during and out of birch pollen season compared to healthy controls 48 . In addition, it has been shown in patients with intermittent 49 and persistent 38 allergic rhinitis that the SCGB1A1 levels in nasal fluid within one hour after allergen challenge correlate inversely with the symptoms of rhinitis. To the best of our knowledge, the role of other SCGBs in allergic rhinitis has not yet been described.…”
Section: Secretoglobins In Diseases Of the Upper And Lower Airwaysmentioning
confidence: 99%
“…The SCGB family is involved in many diseases of the upper and lower airways 36‐38 . In this review, we collected literature on acute (allergic rhinitis and common cold) and chronic airway diseases (allergic asthma, COPD, and cystic fibrosis).…”
Section: Secretoglobins In Diseases Of the Upper And Lower Airwaysmentioning
confidence: 99%
“…Han et al [ 7 ] found that serum IL-1 β levels were elevated in the AR children, especially in severe persistent patients, and positively correlated with disease severity. A recent publication reported that several biomarkers were changed in nasal fluid-persistent AR patients, and Clara cell protein 16 (CC16) showed an inverse correlation with symptom scores [ 14 ]. However, relatively few studies have determined the multiple cytokine profiling in the peripheral blood of AR patients.…”
Section: Introductionmentioning
confidence: 99%